Impact of Kegel Exercise on Brink Scale and Activities of Daily Life(ADLs) in Patients of Cystocele - Taqdees Naqaish , Farwa Rizvi ,Javaid Iqbal Khattak (Journal of Rawalpindi Medical College, 2013)
Background : To study the impact of Kegel exercise on Brink scale and ADLs (Activities of daily life scale) in patients of Cystocele Methods: In this randomized control trial 50 patients of cystocoele (25 each) were divided into two groups. Kegel’s and postural correction exercises were introduced to the experimental group and back strengthening and postural correction exercises to the control group. In Kegel’s exercise alternate contraction and relaxation of pelvic floor and perineal muscles were performed for the treatment of urinary stress incontinence and to strengthen the pelvic floor muscles. Back strengthening exercises were performed by doing 5 repetitions x 2 sets and gradually 10 x 2-3 sets each day, at least for 4 months. Patients were asked to lie flat on back. Results: In the Brink scale, 30% had 3-6 PFM (Pelvic floor muscle) power,48% had power between 7-9, while 22% had 10-12 power. Twenty seven (54%) subjects had no pelvic heaviness after performing Kegel’s exercises, 34% subjects had slight pelvic heaviness, while only 12% subjects had moderate pelvic heaviness. Nine (18%) subjects out of 50 (100%) found difficulty in ADLs (Activities of daily life scale) and had limited activities, while 28% females had little limitation in ADLs, while 54% females were not limited at all in ADLs, after performing Kegel exercises. The results showed that Kegel exercises proved effective on improvement of brink scale (p=0.000), pelvic heaviness (p=0.001), and ADLs (p=0.007). Conclusion: Kegel exercises are significantly effective in improving brink scale, pelvic heaviness, and ADLs (Activities of daily life scale).